Alterations of drug-metabolizing enzymes and transporters under diabetic conditions: what is the potential clinical significance?. (3rd July 2018) - Chen, Feng; Li, De-Yi; Zhang, Bo; Sun, Jie-Yu; Sun, Fang; Ji, Xing; Qiu, Jin-Chun; Parker, Robert B.; Laizure, S. Casey; Xu, Jing
Abstract: There will be 642 million people worldwide by 2040 suffering from diabetes mellitus. Long-term multidrug therapy aims to achieve normal glycemia and minimize complications, and avoid severe hypoglycemic events. The appreciation of the drug-metabolizing enzymes and drug transporters as critical players in the treatment of diabetes has attracted much attention regarding their potential alterations in the pathogenesis of the disease. This review discusses pharmacokinetics-based alterations of cytochrome P450 enzymes, phase-II metabolizing enzymes, and membrane transporter proteins, as well as the potential mechanisms underlying these alterations. We also discuss the potential influences of altered enzymes and transporters on the disposition of commonly prescribed glucose-lowering medicines. Future studies should delve into the impact of altered drug-metabolizing enzymes and transporters on the progression toward abnormal glucose homeostasis.